Computing normal forms and formal invariants of dynamical systems by means of word series. (June 2016) - Murua, A.; Sanz-Serna, J.M.
Abstract: We show how to use extended word series in the reduction of continuous and discrete dynamical systems to normal form and in the computation of formal invariants of motion in Hamiltonian systems. The manipulations required involve complex numbers rather than vector fields or diffeomorphisms. More precisely we construct a group G ¯ and a Lie algebra g ¯ in such a way that the elements of G ¯ and g ¯ are families of complex numbers; the operations to be performed involve the multiplication ★ in G ¯ and the bracket of g ¯ and result in universal coefficients that are then applied to write the normal form or the invariants of motion of the specific problem under consideration.